INCREASING THE DOSE OF A SELECTIVE ANTIMUSCARINIC MEDICATION HELPS IMPROVE THE KEY SYMPTOMS OF OVERACTIVE BLADDER - Kasimov S. S.; Rahmonberdiyev Kh. K. (Modern American Journals, 2025)
Overactive bladder (OAB) is a serious urinary disorder affecting at least 17% of individuals over the age of 40. In most cases, treatment for OAB begins with pharmacological therapy. Currently, medications that block muscarinic receptors in the bladder are most commonly used. Among these medications, solifenacin stands out due to its high selectivity for the bladder compared to other muscarinic antagonists. The studies presented in this article demonstrate that a flexible dosing approach with solifenacin can effectively improve OAB symptoms with minimal impact on tolerability. Based on numerous studies, both the positive effect of increasing the solifenacin (Vesicare) dose on the key symptoms of OAB and the relevance of starting therapy with a 10 mg dose are confirmed. Unlike oxybutynin, this medication does not significantly affect cognitive function in elderly patients. Thus, solifenacin 10 mg, with its optimal balance of efficacy and safety, provides better treatment adherence compared to other muscarinic antagonists.
Keywords: Overactive bladder, muscarinic antagonists, solifenacin 5/10 mg.